2021
DOI: 10.1002/nbm.4563
|View full text |Cite
|
Sign up to set email alerts
|

Chemical exchange saturation transfer imaging for epilepsy secondary to tuberous sclerosis complex at 3 T: Optimization and analysis

Abstract: The homeostasis of various metabolites is impaired in epilepsy secondary to the tuberous sclerosis complex (TSC). Chemical exchange saturation transfer (CEST) imaging is an emerging molecular MRI technique that can detect various metabolites and proteins in vivo. However, the role of CEST imaging for TSC‐associated epilepsy has not been assessed. Here, we aim to investigate the feasibility of applying CEST imaging to TSC‐associated epilepsy, optimize the CEST acquisition parameters, and provide an analysis met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Here, the 3.5 ppm frame is selected as the calibration one because it is critical for APTw imaging and contributes a major part of the SNR in the asymmetry analysis result. But the calibration frame does not have to be at 3.5 ppm, and the KIPI method can be easily adapted for other CEST imaging applications by using calibration frames at different frequency offsets, such as for glutamate 13,14 or glucose 7,8 imaging. However, it should be noted that the calibration frame must have sufficient SNR for calculating the sensitivity maps, and the best calibration frequency needs to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the 3.5 ppm frame is selected as the calibration one because it is critical for APTw imaging and contributes a major part of the SNR in the asymmetry analysis result. But the calibration frame does not have to be at 3.5 ppm, and the KIPI method can be easily adapted for other CEST imaging applications by using calibration frames at different frequency offsets, such as for glutamate 13,14 or glucose 7,8 imaging. However, it should be noted that the calibration frame must have sufficient SNR for calculating the sensitivity maps, and the best calibration frequency needs to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the amine pool plays a dominant role in the contrast between the cortical tubers and normal tissues. These results indicate that CEST MRI may serve as a potentially useful tool for identifying epileptogenic tubers in TSC 37 . Magnetoencephalography and ictal single‐photon emission computed tomography (SPECT) have also been used for the preoperative evaluation of TSC‐related DRE 38,39 .…”
Section: Preoperative Evaluationsmentioning
confidence: 99%
“…These results indicate that CEST MRI may serve as a potentially useful tool for identifying epileptogenic tubers in TSC. 37 Magnetoencephalography and ictal single-photon emission computed tomography (SPECT) have also been used for the preoperative evaluation of TSC-related DRE. 38,39 The epileptogenic tuber was defined in the same brain region on scalp EEG.…”
Section: Preoper Ative E Valuationsmentioning
confidence: 99%
“…A latest study demonstrated successful detection of tubers in patients with epilepsy secondary to the tuberous sclerosis complex using 3 T CEST and suggested that amine protons might be the major contributor to the elevated CEST signal in tubers. 18 Thus, we hypothesize that CEST MRI can predict seizure laterality of TLE at 3 T.…”
Section: Introductionmentioning
confidence: 96%
“…Chemical exchange saturation transfer (CEST) imaging is an emerging MRI technique that can detect proteins and metabolites noninvasively through the exchange of protons between biomolecules and free water. 14 , 15 The exchange rate of amine protons in glutamate is in the slow to intermediate exchange regime (∼2000–∼5000 s −1 ) 15 , 16 , 17 , 18 with respect to its chemical shift at 7 T (∼5600 rad/s), making glutamate an ideal target metabolite for CEST detection at 7 T or higher field strength. Notably, glutamate plays a crucial role in the generation and maintenance of seizures, as demonstrated by both human 19 and animal 20 studies.…”
Section: Introductionmentioning
confidence: 99%